REVIEW OF THE STRENGTH OF FOX GLUE IN DEVELOPMENT BOOK VOLS TECHNOLOGY USING THE YOSHINO 602 ENGINE - Muhammad Sultan Nasution; Nurjalih -; Abdul Majid (Politeknik Negeri Media Kreatif, 2019)
Competition in the manufacture of raw materials for printing and binding purposes is undeniable, as is the hot glue required for binding on books. The method used in this writing is descriptive method, namely by presenting factual information obtained from observations obtained and seen in the Industrial Practices place. The binding technique without thread or perfect binding is used for binding books, magazines and others. The main ingredient in the perfect binding binding process is glue. Glue greatly affects the production result, if the adjustments are not done properly the temperature of the glue and the thickness of the glue. The purpose of writing this paper is to determine the adhesion strength of Fox brand glue and to find out the problems that occur in the gluing unit during the volume of the book